Questions of the effective methods choosing for neutron-physical processes simulation - Prokhorets, I.M.; Prokhorets, S.I.; Rudychev, Y.V.; Khazhmuradov, M.A.; Fedorchenko, D.V. (Вопросы атомной науки и техники, 2007)
One of the possible variants of neutron generator is electron accelerator driven subcritical facility. Analytical method is not appropriate one for designing of this system. Such system is simulated by Monte Carlo methods. The main aim of the presented article is choosing of optimal simulation tools by Monte Carlo methods for solution of the neutron-physical tasks.